Silver nanoparticles synthesized using S. nervosum leaf extract, and their antibacterial and antifungal activity - Hanh, Cong Hong; Hieu, Pham Sy; Nhung, Nguyen Hong; Chi, Tran Que; Huong, Tran Thi; Khanh, Pham Duy; Gam, Pham Thi; Phuong, Nguyen Van; Nga, Phan Thi Thanh; Y, Hoang Hien; et al. (Vietnam Journal of Science and Technology, 2025)
In this study, the green synthesis of silver nanoparticles (AgNPs) was performed using S.nervosum leaf extract, and their physicochemical characterization was also studied. The characteristic surface plasmon resonance peak observed in the visible region at 435 nm is consistent with previous reports of silver nanoparticle formation. The synthesized AgNPs were also characterized by SEM, TEM, XRD, and FTIR, which revealed their nearly spherical shape, with a diameter mainly in the 10 - 30 nm range. The antimicrobial activity of AgNPs was studied using the agar well diffusion method on four clinically significant pathogenic microorganisms (P. aeruginosa ATCC 27853; E. coli ATCC 35218, S. aureus ATCC 12493; S. aureus Mastitis isolate). The results showed that the green-synthesized AgNPs exhibited antimicrobial activity at most studied concentrations, including the antibacterial effect against the S. Aureus (Mastitis isolate) strain, which was found to be resistant to Tetracycline at 100 µg/L. The antifungal activity of these nanoparticles was also studied on Colletotrichum gloeopsoriodes by colony formation assay. The green synthesis of AgNPs was successfully conducted for the first time using the aqueous extract of S. nervosum. The results of this study indicate that the silver nanoparticles have potential applications as antibacterial and antifungal agents.